The contribution of the Court of Justice to the better transposition and implementation of the Framework Agreement on fixed-term work in the field of temporary public employment. The Spanish case - Garate Castro, Javier (LABOS Revista de Derecho del Trabajo y Protección Social, 2024)
The regulation, employment and development of temporary service relations of public employees is, especially in Spain, a frequent cause of conflicts, a part of which appear motivated by alleged incompatibilities with the Framework Agreement on fixed-term work. Doubts about these incompatibilities and their solution have encouraged Spanish judges (of the social order and of the contentious-administrative jurisdictional order) to submit a very high number of requests for a preliminary ruling, which lead to the conviction that temporary public employment has come running and still is running in accordance with a regulatory framework, practices in its use and judicial criteria of interpretation that must be subject to review in order to eliminate its mismatches with EU Labour Law and, in particular, with those declared by the Court of Justice. Notwithstanding the progress made, the Spanish regulation of temporary public employment presents aspects that still do not respond to the requirements of a sufficient transposition of Directive 1999/70/EC, by which the Framework Agreement is applied.